Optimized Sharable-Slot Allocation Using Multiple Channels to Reduce Data-Gathering Delay in Wireless Sensor Networks - Phan Van Vinh; Hoon Oh (Sensors, 2016)
The demand for event-driven real-time applications for timely and reliable data acquisition is growing in industrial sectors. However, it is challenging to satisfy the requirements since constraints such as limited available energy and bandwidth are inherent in a wireless sensor network. To deal with timely delivery, one desirable approach is to improve network throughput so that more real-time applications with tighter time constraints can be satisfied in any given network. To deal with reliable delivery, the use of a carrier sense multiple access mechanism for data transmission is preferred, along with the use of a sharable slot within which multiple nodes compete to send data. Thus, we present a method of using multiple channels and a way to optimize the size of the sharable slot. The proposed channel-slot–scheduling algorithm tries to optimize the size of a sharable slot when multiple channels are used. The algorithm also deals with situations where nodes generate multiple data packets in each round of a data-gathering period. It is shown through simulation that our approach greatly outperforms others on some selected metrics.